2020
DOI: 10.1093/texcom/tgaa019
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Resting-State Functional Connectivity Patterns are More Closely Associated with Severity of Subjective Memory Decline than Whole Hippocampal and Subfield Volumes

Abstract: The goal of this study was to examine whether hippocampal volume or resting-state functional connectivity (rsFC) patterns are associated with subjective memory decline (SMD) in cognitively normal aged adults. Magnetic resonance imaging data from 53 participants (mean age: 71.9 years) of the Boston University Alzheimer’s Disease Center registry were used in this cross-sectional study. Separate analyses treating SMD as a binary and continuous variable were performed. Subfield volumes were generated using FreeSur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Our work adds to a growing body of evidence suggesting that individual differences like intrinsic (i.e., task-free) functional connectivity (Elliott et al, 2019;Finn et al, 2020) and structural properties (Llera et al, 2019) relate to cognition in meaningful ways. Our results join prior research in highlighting the greater sensitivity of connectivity relative to volume-based measures (Yassa et al, 2010;Zajac et al, 2020). Here, we took a hypothesis-rather than a data-driven approach to asking these questions; our analysis was limited to just two hippocampal pathways of greatest expected significance: CA 3 -CA 1 as related to TSP, and ERC-CA 1 as related to MSP.…”
Section: Discussionmentioning
confidence: 54%
“…Our work adds to a growing body of evidence suggesting that individual differences like intrinsic (i.e., task-free) functional connectivity (Elliott et al, 2019;Finn et al, 2020) and structural properties (Llera et al, 2019) relate to cognition in meaningful ways. Our results join prior research in highlighting the greater sensitivity of connectivity relative to volume-based measures (Yassa et al, 2010;Zajac et al, 2020). Here, we took a hypothesis-rather than a data-driven approach to asking these questions; our analysis was limited to just two hippocampal pathways of greatest expected significance: CA 3 -CA 1 as related to TSP, and ERC-CA 1 as related to MSP.…”
Section: Discussionmentioning
confidence: 54%
“…Our work adds to a growing body of evidence suggesting that individual differences like intrinsic (i.e., task-free) functional connectivity (Elliott et al, 2019;Finn et al, 2020) and structural properties (Llera et al, 2019) relate to cognition in meaningful ways. Our results join prior research in highlighting the greater sensitivity of connectivity relative to volume-based measures (Yassa et al, 2010;Zajac et al, 2020). Here, we took a hypothesis-rather than data-driven approach to asking these questions; our analysis was limited to just two hippocampal pathways of greatest expected significance: CA3-CA1 as related to TSP, and ERC-CA1 as related to MSP.…”
Section: Discussionmentioning
confidence: 53%
“…To our knowledge, this is the first report of desynchronization between the ACC and hippocampus being linked with improved working memory performance in any animal model. Given that multiple reports have recently showed that patients with mild cognitive impairment and early AD symptomology have increased connectivity between the hippocampus and cingulate areas 99 , 100 , it is possible that our results provide a potential mechanistic window into how patients are able to overcome these effects during the prolonged prodromic phase of AD. It is possible that short spells of decreased oscillatory coherence are a neural adaptation that minimizes the cognitive impairments of increased connectivity.…”
Section: Discussionmentioning
confidence: 86%